2021
DOI: 10.3390/educsci11100603
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and Learning in Knowledge Spaces (ALEKS) Adaptive System Impact on Students’ Perception and Self-Regulated Learning Skills

Abstract: Adaptive learning is an educational method that uses computer algorithms and artificial intelligence (AI) to customize learning materials and activities based on each user’s model. Adaptive learning has been used for more than 20 years. However, it is still unique, and no other system could bring more or even similar capabilities than the ones adaptive technology offers, including the application of AI, psychology, psychometrics, machine learning, and providing a personalized learning environment. However, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…These measures could help improve communication flows and increase student satisfaction. These results agree with those of Schwanenberger et al [14] and Harati et al [13], who demonstrated that administrative officers need to improve their technological support to offer optimal communication to the student [19]. Furthermore, this could help free teachers from administrative functions and allow them to focus on their teaching tasks [1,3,12].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These measures could help improve communication flows and increase student satisfaction. These results agree with those of Schwanenberger et al [14] and Harati et al [13], who demonstrated that administrative officers need to improve their technological support to offer optimal communication to the student [19]. Furthermore, this could help free teachers from administrative functions and allow them to focus on their teaching tasks [1,3,12].…”
Section: Discussionsupporting
confidence: 88%
“…Sosa Díaz et al [4] and Van-Der-Velde et al [12] studied student satisfaction in the online classroom, concluding that communication skills through ICTs are necessary in the learning process both for accessing training content and to ensure optimal communication between the student and the other university worker's profiles-mainly lecturers and administrative staff. This opinion is shared by Harati et al [13] and Schwanenberger et al [14], who observed it both in students and in university administrative officers in online teaching. Obtaining timely feedback from lecturers in the evaluation process was crucial for students during online education in the pandemic period [15][16][17].…”
Section: Communication In He In the Pandemic Period: Literature Reviewmentioning
confidence: 89%
“…The developed adaptive learning management system, namely Dyslexia Adaptive E-Learning Management System (DAELMS), proves that when the system provides the user with learning materials that match their learning style or dyslexia type, it improves their learning outcomes (Alsobhi et al, 2019). This adaptive learning system was also discussed in research that had been done by (Kazimzade, et al, 2019;Picciano, 2019;Harati et al, 2021). Meanwhile, Krechetov and Romanenko (2020) has proposed a genetic algorithm to exploit adaptive learning technology and technique to create an autonomous system of teacher-less learning as an effective student profiling tool in e-learning, providing teachers with extensive student performance analytics and allowing them to adjust individual learning paths.…”
Section: Adaptive Learningmentioning
confidence: 90%
“…When there is no direct access to in-person instructors, adaptive learning, as a new form of online learning, can focus on the needs of each learner and assist them with their learning process by adapting learning materials based on their knowledge level and personalizing their learning path (Harati et al, 2021).…”
Section: Adaptive Learningmentioning
confidence: 99%
“…All students enrolled in GC1 were directed to complete the ALEKS initial knowledge check in the weeks leading up to the start of the semester. During the adaptive knowledge check, ALEKS accurately assessed student knowledge of all the topics included in the course (209 topics total, on average), and prepared each student’s custom learning pathway. Of the topics that were included in ALEKS, roughly half were considered by the course instructors to be prerequisite and foundational for GC1 (approximately 100 topics). Students were expected to demonstrate mastery of these prerequisite topics during the initial knowledge check or to work in ALEKS to learn these topics before the start of the semester.…”
Section: Methodsmentioning
confidence: 99%